Efluxo de CO2 do solo em sistemas de produção de palma de óleo na Amazônia Oriental - COSTA, Alessa Nayhara Mendanha (Universidade Federal do Pará, 2019)
Tropical forest areas play an important role in the global carbon cycle. However, anthropogenic disturbances have altered the structure of the ecosystem and consequently imply in the carbon budget. To evaluate how changes in land use influence the efflux of CO2 from the soil (the main pathway of CO2 displacement in soil to atmosphere), it is possible to understand how the different types of vegetation affect the CO2 efflux of the soil, evaluating the variables that contribute to this process. A greater understanding of this influence motivates the study in different ecosystems, which seek to identify and develop practices that increase carbon stock and nutrient cycling, such as agroforestry systems (SAFs). Due to the expressive expansion of the oil palm in the Amazon region, the objective of this research was to evaluate the effects of CO2 efflux from the soil, as well as its control variables, in two oil palm production systems (conventional palm oil production systems and agroforestry systems with oil palm). The research was developed in the municipality of Tomé-Açu in areas of family farming and production. Soil CO2 efflux, soil temperature and soil gravimetric moisture were evaluated between March 2016 and November 2016. The stocks of fine roots and litter in the systems were evaluated in the period of higher precipitation (May) and lower precipitation (October). Soil CO2 efflux was higher in successional forest areas, intermediate in oil palm agroforestry systems, and lower in conventional palm oil systems. The CO2 efflux of the soil is sensitive to the "conversion" of forest areas into oil palm crops. The "soil metabolism" in the more diversified oil palm (SAF) system is more similar to that of the more ecologically integrated system (secondary forest).